In vitro assessment of physiological changes of watermelon (Citrullus lanatus) upon iron oxide nanoparticles exposure - Wang, Yunqiang (Plant physiology and biochemistry : PPB, 2016)
Copyright © 2016 Elsevier Masson SAS. All rights reserved.